Kebebasan Manusia dan Konflik dalam Pandangan Eksistensialime Jean Paul Sartre - Muzairi Muzairi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
It is important to understand Jean Paul Sartre’s mode of dualism in order to comprehend Sartre’s notion on humanbeings, freedom and conflict. As a man of ontological basis, Sartre put himself as a radical dualist in that it develops a number of ideas such as the meaning of objective and subjective reality, human existence and life. Those thoughts truly reveal the dark side of being in that it exemplifies the conflict in inter-human relationship context. Sartre discusses the objective meaning (en-soi) or “being-in-self”. For Sartre, en-soi is subject matter or the object of understanding that goes beyond human mind or the being of unconscious self. Unlike pour-soi(foritself) that only awares of itself, it denotes the dual characteristics of human that both awares of subject and the inner self. Human serves both as subject and object. Sartre argues that ‘Pour-soi’ underlining the notion of ‘the nihilation” of Being-in-itself’. In a concise word, “man presents himself…as a being that causes of ‘the nihilation’ of ‘Being in-itself” triggered freedom and conflict.